RELATIONSHIP LEADERSHIP OF THE CHAIRMAN WITH THE EMPOWERMENT LEVEL OF FARMER GROUPS ON CHILI FARMING MANAGEMENT IN BAWANG DISTRICT, BATANG REGENCY - Hendro Sarjito; Siwi Gayatri; Tutik Dalmiyatun (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2019)
Increasing intitutional capacities among ther farmer’s is one of the key to improve farmer’s welfare. This research was conducted with the aim to analyze the relationship between the leadership of the farmer group and the level of empowerment among chili farmer’s in Bawang District, Batang Regency. The study was conducted in  20 December 2018 to 15 January 2019 in Bawang District, Batang Regency. The research method used in this study was the survey method 75 respondent were taken by the complete enumeration method. Data collection was done by using questionnaires, interviews, and direct observations in the field. Data analysis was using descriptive analysis and Rank Spearman correlation test. The results of the study showed that the level of empowerment in management of chili farming system was in medium category. The leadership level of the head of the farmer group in Bawang District were in the category of being able to lead farmer groups. There was a significant relationship between the leadership of the farmer group leader and the level of empowerment of the management of chili farming system in Bawang District, Batang Regency. Keywords: leadership, empowerment, management of chili farming system